(untitled) (Malaysian Journal of Civil Engineering, 2018)
Cities in the developing world are faced with a challenge from the transport intensive land use development focused on personalized modes. Transit Oriented Development (TOD) is considered to be one of the most promising alternative city development strategies focusing on use of public transport. However, most of the high capacity public transport projects in cities of developing countries are coming up at a stage where the city corridors are already developed. Success of a public transport system depends on accessibility of passengers to its nodes. Field data collected from Gazipur Bangladesh shows accessibility to proposed BRT stations depends majorly on access road widths, besides it also depends on road condition, distance of access roads from BRT stations. Potential access roads are ranked with a scoring system and in-situ improvements are proposed to yield achievable results. Retrofitting improvement measures can enhance accessibility and increase ridership. To retain a sustainable path in urban transport, a city needs to improve its accessibility to Public Transport nodes that will ensure a viable public transport system, which is a prerequisite to a successful TOD.